Islamic medical practice: a holistic approach to patient care in Sharia-compliant hospitals - Mohd Yusof, Nazri (Kulliyyah of IIUM, 2023)
With great advancements in medical research and technology, the practice of medicine has increasingly detached itself from the human touch and the actual practice of the art of medicine. Management of patients has become very technical, thus focusing on the imaging and laboratory results rather than focusing on patients as people with bodies and souls